THE GENDER EQUALITY CAMPAIGN IN PICTURE STORY AL-BINTU MITSLUL WALAD (A ROLAND BARTHES’S SEMIOTICS STUDY) - Mamat Rachmat; Firstiyana Romadlon Ash Shidiqiyah; Ahmad Syakir Maulana (CMES (Center of Middle Eastern Studies), 2023)
The picture story "Al-Bintu Mitslu al-Walad" by Fatimah Al-Ma’dul narrates the tale of a child named Salma who seeks justice for her rights in the arena of games. As a child, Salma demands an end to discrimination between girls and boys in choosing games. This article highlights Salma's childhood character and the equality she advocates. The research employs a qualitative descriptive method that focuses on describing the narrative and visual aspects of the book and interprets them from Roland Barthes' semiotic perspective. From Barthes' perspective on myth, the meaning of the struggle for gender equality represents the gender equality campaign of Hosni Mubarak, the leader of Egypt from 1981 to 2011. Semiotically, the book reinforces Mubarak's policies regarding gender equality in Egypt, thereby not being considered mere rhetoric. Therefore, this book is presented as a way to seek support from the community.